2019
DOI: 10.1089/apc.2018.0166
|View full text |Cite
|
Sign up to set email alerts
|

Considering Stigma in the Provision of HIV Pre-Exposure Prophylaxis: Reflections from Current Prescribers

Abstract: Efforts to identify and address social inequities in HIV pre-exposure prophylaxis (PrEP) access are urgently needed. We investigated early-adopting PrEP prescribers' beliefs about how stigma contributes to PrEP access disparities in health care and explored potential intervention strategies within the context of PrEP service delivery. US-based PrEP prescribers were recruited through professional networks and participant referrals. Qualitative interviews were conducted, transcribed, and thematically analyzed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 53 publications
3
56
0
Order By: Relevance
“…Perceptions of having low-risk patient populations while working in geographic areas with high prevalence of HIV infection suggest that education regarding local HIV epidemiology may be warranted to ensure that PCPs are aware; this may help PCPs take every opportunity to provide HIV prevention and education during clinical visits with patients. Previous research has shown that providers may hold misconceptions about patients, including age-related stereotypes (i.e., older patients being sexually inactive), 25 which our data corroborate.…”
Section: Geographic Information System Results/analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Perceptions of having low-risk patient populations while working in geographic areas with high prevalence of HIV infection suggest that education regarding local HIV epidemiology may be warranted to ensure that PCPs are aware; this may help PCPs take every opportunity to provide HIV prevention and education during clinical visits with patients. Previous research has shown that providers may hold misconceptions about patients, including age-related stereotypes (i.e., older patients being sexually inactive), 25 which our data corroborate.…”
Section: Geographic Information System Results/analysissupporting
confidence: 86%
“…HIV-related stigma exhibited by health care workers in the South is prevalent, and provider characteristics such as race, religion, and clinic type may predict stigmatizing attitudes. [26][27][28] Research has also shown that personal values held by providers may interfere with discussing sexual behaviors with their patients, 25 and patient anticipated stigma in health care settings has been correlated with lower adherence to ART. 29 This underscores that targeted educational and stigma reduction efforts with providers in the southern United States, like those who participated in this study, are warranted.…”
Section: Geographic Information System Results/analysismentioning
confidence: 99%
“…Once implemented, the effect of PrEP availability on these outcomes should be monitored and evaluated. Despite the importance of monitoring this potential unintended consequence of PrEP use, previous evidence suggests that PrEP use does not necessarily lead to risk compensation and cessation of condom use, but rather enhances informed choices [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that stigma and biases were influential barriers to PrEP prescription. 24,26,30,36,42,44,48 In one qualitative study, researchers highlighted the negative influence of providers' race, gender, and age biases on PrEP decision-making. Physicians described how their own personal values related to sex, including discussing sexual activity with LGBTQ individuals, were barriers to PrEP prescription.…”
Section: Interpersonal Stigmamentioning
confidence: 99%